Baseline Neurocognitive Performance and Symptoms in Those With Attention Deficit Hyperactivity Disorders and History of Concussion With Previous Loss of Consciousness - Kaye, Sarah; Sundman, Mark H.; Hall, Eric E.; Williams, Ethan; Patel, Kirtida; Ketcham, Caroline J. (Frontiers in Neurology, 2019)
Previous consensus statements on sports concussion have highlighted the importance of Attention Deficit Hyperactivity Disorder (ADHD and loss of consciousness (LOC) as risk factors related to concussion management. The present study investigated how self-reported history of either Attention Deficit Hyperactivity Disorder (ADHD) diagnosis or history of previous concussion resulting in loss of consciousness ( LOC) influence baseline neurocognitive performance and self-reported symptoms. This analysis was performed retrospectively on data collected primarily from student-athletes, both Division 1 and club sports athletes. The dataset (n=1460) is comprised of college students (age = 19.1 ± 1.4 years). Significant differences were found for composite scores on the ImPACT for both history of concussion (p = .016) and ADHD (p = .014). For concussion history, those with a previous concussion, non-LOC, performed better on the visual motor speed (p = .004). Those with diagnosis of ADHD performed worse on verbal memory (p = .001) and visual motor speed (p = .033). For total symptoms, concussion history (p < .001) and ADHD (p = .001) had an influence on total symptoms. Those with ADHD reported more symptoms for concussion history; those with previous LOC concussion reported more symptoms than those with non-LOC concussion (p=.003) and no history (p < .001). These results highlight the importance of assessing baseline measures pre-season neurocognitive function and symptoms that can later be referenced in concussion management in order to account for group differences mediated by pre-existing conditions such as ADHD and LOC from previous concussion that could influence these measures.